(untitled) (City: History, Culture, Society, 2023)
In Ukrainian historiography, the study of the gastronomic culture of ancient societies is gaining prominence. The nutrition of the burghers and peasants of Volhynia at the end of the 15th century to the middle of the 16th century has not yet been the topic of an independent study. In addition, historians frequently overlook the usage of alcohol and its importance in the daily lives of the medieval populace. The purpose of this work is to clarify the characteristics of research materials on alcoholic beverages, as well as to identify the types of beverages, sites of consumption, and the function of alcohol in the daily lives of Volhynian townspeople and peasants. Our research has led us to the conclusion that the analysis of the public judicial acts, the records of the Grand Ducal Chancellery, and the deeds of sale and purchase contain certain features that, when combined, assist us to depict alcoholic beverages. It was discovered that the inhabitants of Volhynia drank low-alcohol beer on a daily basis, whereas wine was a status symbol for the elite. In addition, the geographical and climatic conditions of Volhynia influenced the types of beverages because they encouraged the cultivation of particular grains. The cereals were utilized to make malt. In the 16th century, vodka’s popularity grew. The potency of alcoholic beverages varied and played a significant impact in the lives of medieval people. On the one hand, alcoholic beverages were caloric, so individuals received daily energy from them; on the other hand, consuming alcoholic beverages was a vital element of many social interactions. The burghers and peasants could purchase alcoholic beverages at fairs and marketplaces or in guesthouses, but the most popular site was a korchma (a tavern) that mixed drinking with entertainment, such as discussions, dances, and more. The excessive drinking was denounced since it resulted in a variety of negative consequences for society. However, using alcohol in moderation was the norm. In conclusion, the preparation and consumption of beer, mead, and vodka matched to trends in Eastern European countries from the latter half of the 15th century to the middle of the 16th century.